SELECTIVE SEROTONIN REUPTAKE INHIBITORS AND BRUXISM: ASSOCIATION IN A TOTAL PROSTHESIS USER - Cordeiro, Patricia Cataldo de Felipe (2014)
Contrary effects of selective serotonin reuptake inhibitors are one of the risk factors for the development of bruxism and symptomology of temporal-mandibular disorder. The association between several predisposing and aggravating factors for the development of bruxism may be observed in a clinical case involving complaints and therapy of a 53-year-old patient, using unstable total prostheses, with chronic mouth and face pain, temporal-mandibular disorder and headaches attributed to the parafunctional habit. The behavior of symptomatic therapy, directed to the control of risk factors, was defined by the inter-occlusion plate which reduced and stabled the symptomology from the start of the treatment, coupled to guidelines of self-care. The need for a different approach in users of total prostheses was underscored since the patients may be more prone to psychosocial disorders caused by loss of teeth and adaptation to the prosthesis.